Burden and outcomes of postpartum haemorrhage in Nigerian referral-level hospitals. (2024)
Objective: To determine the prevalence of primary postpartum haemorrhage (PPH), risk factors, and maternal and neonatal outcomes in a multicentre study across Nigeria. Design: A secondary data analysis using a cross-sectional design. Setting: Referral-level hospitals (48 public and six private facilities). Population: Women admitted for birth between 1 September 2019 and 31 August 2020. Methods: Data collected over a 1-year period from the Maternal and Perinatal Database for Quality, Equity and Dignity programme in Nigeria were analysed, stratified by mode of delivery (vaginal or caesarean), using a mixed-effects logistic regression model. Main outcome measures: Prevalence of PPH and maternal and neonatal outcomes. Results: Of 68 754 women, 2169 (3.2%, 95% CI 3.07%–3.30%) had PPH, with a prevalence of 2.7% (95% CI 2.55%–2.85%) and 4.0% (95% CI 3.75%–4.25%) for vaginal and caesarean deliveries, respectively. Factors associated with PPH following vaginal delivery were: no formal education (aOR 2.2, 95% CI 1.8–2.6, P < 0.001); multiple pregnancy (aOR 2.7, 95% CI 2.1–3.5, P < 0.001); and antepartum haemorrhage (aOR 11.7, 95% CI 9.4–14.7, P < 0.001). Factors associated with PPH in a caesarean delivery were: maternal age of >35 years (aOR 1.7, 95% CI 1.5–2.0, P < 0.001); eferral from informal setting (aOR 2.4, 95% CI 1.4–4.0, P = 0.002); and antepartum haemorrhage (aOR 3.7, 95% CI 2.8–4.7, P < 0.001). Maternal mortality occurred in 4.8% (104/2169) of deliveries overall, and in 8.5% (101/1182) of intensive care unit admissions. One-quarter of all infants were stillborn (570/2307), representing 23.9% (429/1796) of neonatal intensive care unit admissions. Conclusions: A PPH prevalence of 3.2% can be reduced with improved access to skilled birth attendants.